1998
DOI: 10.1046/j.1365-2141.1998.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of the effect of clodronate on skeletal morbidity in multiple myeloma

Abstract: In patients with multiple myeloma, despite a major reduction of bone pain achieved with chemotherapy, skeletal disease continues to progress. The effects of clodronate, an inhibitor of osteoclastic bone resorption, are evaluated on the natural history of skeletal disease in patients with newly diagnosed multiple myeloma. Within the framework of the VIth MRC Multiple Myeloma Trial, 536 patients (218 women, 318 men) with recently diagnosed multiple myeloma were randomized to receive either clodronate 1600 mg dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
167
0
5

Year Published

2000
2000
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(173 citation statements)
references
References 32 publications
1
167
0
5
Order By: Relevance
“…There is the important possibility that the survival of patients may be prolonged [107][108][109] in some groups of patients. Recently, osteonecrosis of the jaw 110 was identified as a potential complication of high-dose bisphosphonate therapy in malignant diseases.…”
Section: Clinical Applications Of Bisphosphonatesmentioning
confidence: 99%
“…There is the important possibility that the survival of patients may be prolonged [107][108][109] in some groups of patients. Recently, osteonecrosis of the jaw 110 was identified as a potential complication of high-dose bisphosphonate therapy in malignant diseases.…”
Section: Clinical Applications Of Bisphosphonatesmentioning
confidence: 99%
“…8 Clinical studies have suggested that BPs may induce a reduction of the tumor burden 9 and may prolong the survival of MM patients. 10,11 We have evaluated if the combination of zoledronate (Zln), a potent antiresorptive BP, 12 and dexamethasone (Dex), which is commonly used in the treatment of MM, could strengthen the inhibition of cell growth and the induction of apoptosis in human myeloma cell lines in vitro. Here, we show that the combination of both agents results in synergistic anti-myeloma effects, providing a rationale for in vivo investigations on this therapeutical combination.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years bisphosphonates have become important in the management of cancer-induced bone disease and are now well established in the management of patients with multiple myeloma and bone metastases secondary to breast cancer (Paterson et al, 1993;Berenson et al, 1996;Hortobagyi et al, 1996;Diel et al, 1998;McCloskey et al, 1998;Theriault et al, 1999). Randomized controlled trials in patients with breast cancer have demonstrated that clodronate and pamidronate reduce skeletal morbidity and improve quality of life (Paterson et al, 1993;Hortobagyi et al, 1996;Kanis et al, 1996).…”
mentioning
confidence: 99%